Aluminum environmentally friendly decorative material formula based on negative ion decomposition of formaldehyde

By designing an aluminum environmentally friendly decorative material formula containing negative ion powder and other functional components, the problem that existing aluminum environmentally friendly decorative materials cannot purify indoor air is solved, and multiple effects such as air purification, antibacterial and long-term stability are achieved.

CN119752212AInactive Publication Date: 2025-04-04GUIZHOU JIAALUMINUM DECORATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046912.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing aluminum environmentally friendly decorative materials lack the ability to decompose formaldehyde by negative ions and cannot effectively purify indoor air, resulting in insufficient improvement in indoor air quality, short service life of the material, and poor decorative effect and functional stability.

Method used

A formula for environmentally friendly aluminum decorative materials based on negative ions decomposing formaldehyde was designed, including aluminum powder, modified resin, tourmaline powder, nanotitanium dioxide, negative ion powder, silica microspheres, fillers, stabilizers, dispersants, plasticizers, coupling agents, antibacterial agents and pigments. Through specific formula ratios and process flow, the materials can effectively release negative ions, purify the air and have antibacterial properties.

Benefits of technology

The material purifies the air through negative ions, significantly improving the freshness and comfort of indoor air, enhancing antibacterial properties, extending the service life of the material, and ensuring its long-term decorative effect and functional stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum environmentally friendly decorative materials, in particular to a formula of aluminum environmentally friendly decorative materials based on decomposing formaldehyde by negative ions. The formula comprises the following components by mass percentage: 10% to 40% of aluminum powder, 20% to 30% of modified resin, 5% to 12% of tourmaline powder, 2% to 5% of nano titanium dioxide, 5% to 8% of negative ion powder, 3% to 8% of silicon dioxide microspheres, 5% to 10% of filler, 1% to 2% of stabilizer, 0.5% to 1% of dispersant, 1% to 3% of plasticizer, 0.5% to 1% of coupling agent, 0.5% to 1% of antibacterial agent, 0% to 5% of pigment, and the balance is water. The invention has good decorative performance, negative ion air purification function, antibacterial performance and physical and mechanical properties, can be widely used in the field of indoor and outdoor decoration, and creates a beautiful, comfortable and healthy living and working environment for people.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum environmentally friendly decorative materials, and in particular to a formula of aluminum environmentally friendly decorative materials based on decomposition of formaldehyde by negative ions. Background Art

[0002] Aluminum environmentally friendly decorative materials are a new type of decorative material with aluminum as the main component, which integrates environmental protection concepts and advanced technologies. It is widely used in construction, home furnishing and other fields. Aluminum easily reacts with oxygen in the air to form a dense aluminum oxide film on the surface. It has good corrosion resistance and can effectively resist the erosion of acids, alkalis, salts and other chemical substances, thereby ensuring the service life of the decorative materials.

[0003] Most of the existing aluminum environmentally friendly decorative materials are made of a single aluminum material. During daily use, they do not have the ability to decompose formaldehyde with negative ions and cannot purify indoor air. They are insufficient in improving indoor air quality and also reduce the service life of the material, making it impossible to guarantee its long-term decorative effect and functional stability.

[0004] Therefore, most of the above-mentioned aluminum environmentally friendly decorative materials are prepared by a single aluminum material, and do not have the ability to decompose formaldehyde with negative ions during daily use, and cannot purify indoor air, and are insufficient in improving indoor air quality. A formula of aluminum environmentally friendly decorative materials based on negative ion decomposition of formaldehyde can be designed. Summary of the invention

[0005] In order to overcome the problem that most aluminum environmentally friendly decorative materials are made of a single aluminum material, they do not have the ability to decompose formaldehyde with negative ions during daily use, cannot purify indoor air, and are insufficient in improving indoor air quality.

[0006] The technical scheme of the present invention is: the formula of aluminum environmentally friendly decorative material based on decomposing formaldehyde by negative ions comprises the following components by mass percentage: 10% to 40% of aluminum powder, 20% to 30% of modified resin, 5% to 12% of tourmaline powder, 2% to 5% of nano titanium dioxide, 5% to 8% of negative ion powder, 3% to 8% of silicon dioxide microspheres, 5% to 10% of filler, 1% to 2% of stabilizer, 0.5% to 1% of dispersant, 1% to 3% of plasticizer, 0.5% to 1% of coupling agent, 0.5% to 1% of antibacterial agent, 0.5% to 1% of pigment and the balance is water.

[0007] Preferably, the filler includes carbonate, silicate and barium sulfate 1% to 3%, carbonate includes heavy calcium carbonate 5% to 8% and light calcium carbonate 3% to 6%, silicate includes talc 3% to 7% and kaolin 2% to 5%.

[0008] Preferably, the stabilizer includes a metal soap stabilizer, an organic tin stabilizer and a composite stabilizer. The metal soap stabilizer includes 1% to 1.15% calcium zinc stabilizer and 0.5% to 1% barium cadmium stabilizer. The organic tin stabilizer includes 0.8% to 1.2% methyl tin mercaptan stabilizer and 0.5% to 1% octyl tin stabilizer. The composite stabilizer includes 0.8% to 1.5% rare earth composite stabilizer and 0.5% to 1.2% polymer composite stabilizer.

[0009] Preferably, the dispersant includes an inorganic dispersant, an organic small molecule dispersant and a polymer dispersant. The inorganic dispersant includes 0.5% to 1% sodium hexametaphosphate and 0.3% to 0.8% sodium tripolyphosphate. The organic small molecule dispersant includes 0.2% to 0.5% stearic acid and 0.1% to 0.3% triethanolamine. The polymer dispersant includes 0.8% to 1.5% polycarboxylate and 0.5% to 1% polyacrylate.

[0010] Preferably, the plasticizer includes phthalates, aliphatic dibasic acid esters and epoxy plasticizers, the phthalates include 3% to 5% dioctyl phthalate and 4% to 6% diisononyl phthalate, the aliphatic dibasic acid esters include 5% to 8% dioctyl adipate and 6% to 9% dioctyl sebacate, and the epoxy plasticizer includes 5% to 10% epoxidized soybean oil and 4% to 8% epoxy fatty acid methyl ester.

[0011] Preferably, the coupling agent includes a silane coupling agent and a titanate coupling agent. The silane coupling agent includes 0.5% to 1.5% of γ-aminopropyltriethoxysilane and 0.8% to 2% of γ-methacryloxypropyltrimethoxysilane. The titanate coupling agent includes 0.5% to 1% of isopropyltrioleyloxytitanate and 0.6% to 1.2% of isopropyltrititanate.

[0012] Preferably, the antibacterial agent includes inorganic antibacterial agents, organic antibacterial agents and natural antibacterial agents, the inorganic antibacterial agents include 0.1% to 0.5% silver-based antibacterial agents, 0.3% to 0.8% copper-based antibacterial agents and 0.5% to 1% zinc-based antibacterial agents, the organic antibacterial agents include 0.2% to 0.6% quaternary ammonium salt antibacterial agents, 0.1% to 0.3% biguanide antibacterial agents and 0.1% to 0.4% phenolic antibacterial agents, and the natural antibacterial agents include 0.5% to 1.5% chitosan and 0.3% to 0.8% plant extracts.

[0013] The present invention also provides a method for preparing an environmentally friendly aluminum decorative material based on the decomposition of formaldehyde by negative ions, which comprises the formula of the environmentally friendly aluminum decorative material based on the decomposition of formaldehyde by negative ions as described above, and the steps are as follows:

[0014] Step 1: placing aluminum powder in a drying oven, sieving it through a sieve after drying, grinding tourmaline powder, nano titanium dioxide and negative ion powder with a planetary ball mill, and then mixing them with a dispersant and water, and dispersing them by ultrasonication;

[0015] Step 2: Add modified resin, plasticizer, stabilizer, dispersant and water into a mixer and stir. Heat appropriately during stirring to form a resin solution. Slowly add the treated tourmaline powder, nano titanium dioxide and negative ion powder into the resin solution in sequence. After mixing evenly, add coupling agent and antibacterial agent and continue stirring for 10 to 15 minutes.

[0016] Step 3: The mixed material is formed through a twin-screw extruder, and the formed product is placed in an oven for curing. After curing, the product surface is polished with sandpaper to remove burrs and flaws on the surface, and then polished with polishing paste. After polishing, the prepared aluminum environmentally friendly decorative material is tested for performance.

[0017] Preferably, the drying temperature is 80-100°C, the drying time is 2-3h, the sieve aperture is 100-200 mesh, the particle size is ground to 1-5 microns, the dispersion time is 30-60min, the temperature of each section of the extruder is 120-140°C in zone 1, 160-180°C in zone 2, 180-200°C in zone 3, 200-220°C in zone 4, the head temperature is 200-230°C, and the screw speed is 30-50 rpm.

[0018] Preferably, the stirring speed is 600-800 rpm, the stirring time is 10-15 min, the heating temperature is 40-60° C. After adding tourmaline powder, nano titanium dioxide and negative ion powder, the stirring speed is increased to 1000-1500 rpm, and the stirring time is continued for 20-30 min.

[0019] The beneficial effects of the present invention are as follows: aluminum powder is the main filling and reinforcing material, which gives the decorative material a certain strength and metallic texture. At the same time, aluminum has good thermal conductivity, which helps to dissipate the heat inside the material and ensure the stability of the material; the modified resin has good adhesion, weather resistance and chemical stability, and can closely combine other components to form a continuous matrix phase, ensuring the integrity and processing performance of the material; tourmaline powder has natural negative ion emission performance, and after ultra-fine treatment, the particle size is 1 to 5 microns, which can be evenly dispersed in the material, continuously release negative ions, react with harmful substances such as formaldehyde and bacteria in the air, and play the role of purifying the air and antibacterial; negative ion powder can further enhance the ability of the material to release negative ions, create an air atmosphere similar to a forest environment, and improve the freshness and comfort of indoor air; Silica microspheres can reduce the density of materials and have good thermal insulation properties and chemical stability, which helps to improve the thermal insulation effect of materials and reduce indoor energy consumption; fillers further fill the gaps inside the materials to reduce costs; stabilizers can prevent the performance of materials from deteriorating due to factors such as heat, light, and oxygen during processing and use, extend the service life of materials, and ensure their long-term decorative effects and functional stability; dispersants avoid agglomeration and improve the physical properties and functional uniformity of materials; coupling agents enhance the interfacial bonding between aluminum powder and resin, improve the compatibility of fillers, negative ion additives, etc. with the matrix, and improve the comprehensive performance of materials; antibacterial agents inhibit the growth and reproduction of microorganisms such as bacteria and mold on the surface of decorative materials, and combined with the negative ion purification function, provide double hygiene protection for the indoor environment. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments.

[0021] Example 1

[0022] The present invention provides an embodiment: a formula of an aluminum environmentally friendly decorative material based on the decomposition of formaldehyde by negative ions, which comprises the following components by mass percentage: 10% aluminum powder, 20% modified resin, 5% tourmaline powder, 2% nano titanium dioxide, 5% negative ion powder, 3% silicon dioxide microspheres, 5% filler, 1% stabilizer, 0.5% dispersant, 1% plasticizer, 0.5% coupling agent, 0.5% antibacterial agent, and the balance is water; the filler comprises carbonate, silicate and 1% barium sulfate, the carbonate comprises 5% heavy calcium carbonate and 3% light calcium carbonate, and the silicate comprises 3% talcum powder. % and kaolin 2%; stabilizers include metal soap stabilizers, organic tin stabilizers and composite stabilizers, metal soap stabilizers include calcium zinc stabilizer 1% and barium cadmium stabilizer 0.5%, organic tin stabilizers include methyl tin mercaptide stabilizer 0.8% and octyl tin stabilizer 0.5%, composite stabilizers include rare earth composite stabilizer 0.8% and polymer composite stabilizer 0.5%; dispersants include inorganic dispersants, organic small molecule dispersants and polymer dispersants, inorganic dispersants include sodium hexametaphosphate 0.5% and sodium tripolyphosphate 0.3%, organic small molecule dispersants include hard The invention discloses a kind of novel nanostructured carbonyl ester, which is a kind of nanostructured carbonyl ester. The nanostructured carbonyl ester comprises a kind of nanostructured carbonyl ester, which is a nanostructured carbonyl ester. The nanostructured carbonyl ester comprises a kind of nanostructured carbonyl ester, which is a nanostructured carbonyl ester. The nanostructured carbonyl ester comprises a kind of nanostructured carbonyl ester, which is a nanostructured carbonyl ester. The nanostructured carbonyl ester comprises a kind of nanostructured carbonyl ester, which is a nanostructured carbonyl ester. The nanostructured carbonyl ester comprises a kind of nanostructured carbonyl ester, which is a nanostructured carbonyl ester. The invention discloses a novel nanostructured carbonyl silane comprising 0.5% alkyl and 0.8% γ-methacryloxypropyltrimethoxysilane, a titanate coupling agent comprising 0.5% isopropyl trioleyloxy titanate and 0.6% isopropyl trititanate; the antibacterial agent comprises an inorganic antibacterial agent, an organic antibacterial agent and a natural antibacterial agent, the inorganic antibacterial agent comprises 0.1% silver-based antibacterial agent, 0.3% copper-based antibacterial agent and 0.5% zinc-based antibacterial agent, the organic antibacterial agent comprises 0.2% quaternary ammonium salt antibacterial agent, 0.1% biguanide antibacterial agent and 0.1% phenolic antibacterial agent, and the natural antibacterial agent comprises 0.5% chitosan and 0.3% plant extract.

[0023] The method for preparing an environmentally friendly aluminum decorative material based on the decomposition of formaldehyde by negative ions comprises the secret formula of the environmentally friendly aluminum decorative material based on the decomposition of formaldehyde by negative ions as described above, and the steps are as follows:

[0024] The aluminum powder was placed in a drying oven at a temperature of 80°C and dried for 3 hours. After drying, it was sieved through a sieve with an aperture of 100 mesh. 5% of tourmaline powder, 2% of nano titanium dioxide and 5% of negative ion powder were ground to 1 mm using a planetary ball mill, and then mixed with 0.5% of dispersant and water, and dispersed by ultrasound for 30 minutes. 20% of modified resin, 1% of plasticizer, 1% of stabilizer, 0.5% of dispersant and water were added to a mixer and stirred at a speed of 600 rpm for 10 minutes. During the stirring process, it was heated to 40°C to form a resin solution. The treated tourmaline powder 5%, nano titanium dioxide 2% and negative ion powder 5% were slowly added to the resin solution in sequence. liquid, increase the stirring speed to 1000 rpm, continue stirring for 20 minutes, add 0.5% coupling agent and 0.5% antibacterial agent after mixing evenly, and continue stirring for 10 minutes; the mixed material is basically formed by a twin-screw extruder, the temperature of each section of the extruder is 120°C in zone 1, 160°C in zone 2, 180°C in zone 3, 200°C in zone 4, the head temperature is 200°C, the screw speed is 30 rpm, the formed product is placed in an oven for curing treatment, and after curing, the product surface is polished with sandpaper to remove burrs and defects on the surface, and then polished with polishing paste. After polishing, the prepared aluminum environmentally friendly decorative material is tested for performance.

[0025] Example 2

[0026] The present invention provides an embodiment: a formula of an aluminum environmentally friendly decorative material based on the decomposition of formaldehyde by negative ions, which comprises the following components by mass percentage: 40% aluminum powder, 30% modified resin, 12% tourmaline powder, 5% nano titanium dioxide, 8% negative ion powder, 8% silicon dioxide microspheres, 10% filler, 2% stabilizer, 1% dispersant, 3% plasticizer, 1% coupling agent, 1% antibacterial agent, 5% pigment, and the balance is water; the filler comprises carbonate, silicate and 3% barium sulfate, the carbonate comprises 8% heavy calcium carbonate and 6% light calcium carbonate, and the silicate comprises lubricant. Stone powder 7% and kaolin 5%; stabilizers include metal soap stabilizers, organic tin stabilizers and composite stabilizers. Metal soap stabilizers include calcium zinc stabilizers 1.15% and barium cadmium stabilizers 1%. Organic tin stabilizers include methyl tin mercaptide stabilizers 1.2% and octyl tin stabilizers 1%. Composite stabilizers include rare earth composite stabilizers 1.5% and polymer composite stabilizers 1.2%. Dispersants include inorganic dispersants, organic small molecule dispersants and polymer dispersants. Inorganic dispersants include sodium hexametaphosphate 1% and sodium tripolyphosphate 0.8%. Organic small molecule dispersants The invention comprises 0.5% stearic acid and 0.3% triethanolamine, the polymer dispersant comprises 1.5% polycarboxylate and 1% polyacrylate; the plasticizer comprises phthalate, aliphatic dibasic acid ester and epoxy plasticizer, the phthalate comprises 5% dioctyl phthalate and 6% diisononyl phthalate, the aliphatic dibasic acid ester comprises 8% dioctyl adipate and 9% dioctyl sebacate, the epoxy plasticizer comprises 10% epoxidized soybean oil and 8% epoxidized fatty acid methyl ester; the coupling agent comprises silane coupling agent and titanate coupling agent, the silane coupling agent comprises γ-aminopropyl tris(III)-1-nitropropanediol ... silane coupling agent comprises γ-aminopropyl tris(III)-1-nitropropanediol; the silane coupling agent comprises γ-aminopropyl tris(III)-1-nitropropanediol; the silane coupling agent comprises γ-aminopropyl tris(III)-1-nitropropanediol; the silane coupling agent comprises γ-aminopropyl tris(III)-1-nitropropanediol; the silane coupling agent comprises γ-aminopropyl tris(III)-1-nitropropanediol; the silane coupling agent comprises γ-aminopropyl tris(III)-1-nitropropanediol; the silane coupling agent comprises γ-aminopropyl tris(III)- 1.5% ethoxysilane and 2% γ-methacryloxypropyltrimethoxysilane, titanate coupling agents include 1% isopropyl trioleyloxy titanate and 1.2% isopropyl triptitanate; antibacterial agents include inorganic antibacterial agents, organic antibacterial agents and natural antibacterial agents, inorganic antibacterial agents include 0.5% silver antibacterial agents, 0.8% copper antibacterial agents and 1% zinc antibacterial agents, organic antibacterial agents include 0.6% quaternary ammonium salt antibacterial agents, 0.3% biguanide antibacterial agents and 0.4% phenolic antibacterial agents, natural antibacterial agents include 1.5% chitosan and 0.8% plant extracts.

[0027] The method for preparing an environmentally friendly aluminum decorative material based on the decomposition of formaldehyde by negative ions comprises the formula of the environmentally friendly aluminum decorative material based on the decomposition of formaldehyde by negative ions as described above, and the steps are as follows:

[0028] The aluminum powder was placed in a drying oven at a temperature of 100°C and dried for 2 hours. After drying, it was sieved through a sieve with an aperture of 200 mesh. 12% of tourmaline powder, 5% of nano titanium dioxide and 8% of negative ion powder were ground to 5 mm using a planetary ball mill, and then mixed with 1% of dispersant and water, and dispersed by ultrasound for 30 minutes. 30% of modified resin, 3% of plasticizer, 2% of stabilizer, 1% of dispersant and water were added to a mixer and stirred at a speed of 800 rpm for 15 minutes. During the stirring process, it was heated to 60°C to form a resin solution. The treated tourmaline powder 12%, nano titanium dioxide 5% and negative ion powder 8% were slowly added to the resin solution in sequence. In the fat solution, increase the stirring speed to 1500 rpm, continue stirring for 30 minutes, add 1% coupling agent and 1% antibacterial agent after mixing evenly, and continue stirring for 15 minutes; the mixed material is basically formed by a twin-screw extruder, the temperature of each section of the extruder is 140°C in zone 1, 80°C in zone 2, 200°C in zone 3, 220°C in zone 4, the head temperature is 230°C, the screw speed is 50 rpm, the formed product is placed in an oven for curing treatment, and after curing, the product surface is polished with sandpaper to remove burrs and defects on the surface, and then polished with polishing paste. After polishing, the prepared aluminum environmentally friendly decorative material is tested for performance.

[0029] The environmentally friendly aluminum decorative material formula using negative ions to decompose formaldehyde in Examples 1 and 2 has good decorative performance, negative ion air purification function, antibacterial performance and physical and mechanical properties, and can be widely used in the field of indoor and outdoor decoration to create a beautiful, comfortable and healthy living and working environment for people.

[0030] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the purpose of the present invention.

Claims

1. A formula of environmentally friendly aluminum decorative material based on the decomposition of formaldehyde by negative ions, characterized in that: Calculated by mass percentage, the invention comprises the following components: 10% to 40% aluminum powder, 20% to 30% modified resin, 5% to 12% tourmaline powder, 2% to 5% nano titanium dioxide, 5% to 8% negative ion powder, 3% to 8% silicon dioxide microspheres, 5% to 10% filler, 1% to 2% stabilizer, 0.5% to 1% dispersant, 1% to 3% plasticizer, 0.5% to 1% coupling agent, 0.5% to 1% antibacterial agent, 0.5% to 1% pigment and the balance is water.

2. The formula of environmentally friendly aluminum decorative material based on decomposition of formaldehyde by negative ions according to claim 1, characterized in that: The fillers include carbonate, silicate and barium sulfate 1% to 3%, carbonate includes heavy calcium carbonate 5% to 8% and light calcium carbonate 3% to 6%, silicate includes talc powder 3% to 7% and kaolin 2% to 5%.

3. The formula of environmentally friendly aluminum decorative material based on decomposing formaldehyde by negative ions according to claim 1, characterized in that: Stabilizers include metal soap stabilizers, organic tin stabilizers and composite stabilizers. Metal soap stabilizers include 1% to 1.15% calcium zinc stabilizer and 0.5% to 1% barium cadmium stabilizer. Organic tin stabilizers include 0.8% to 1.2% methyl tin mercaptan stabilizers and 0.5% to 1% octyl tin stabilizers. Composite stabilizers include 0.8% to 1.5% rare earth composite stabilizers and 0.5% to 1.2% polymer composite stabilizers.

4. The formula of environmentally friendly aluminum decorative material based on decomposition of formaldehyde by negative ions according to claim 1, characterized in that: The dispersants include inorganic dispersants, organic small molecule dispersants and polymer dispersants. The inorganic dispersants include 0.5% to 1% sodium hexametaphosphate and 0.3% to 0.8% sodium tripolyphosphate. The organic small molecule dispersants include 0.2% to 0.5% stearic acid and 0.1% to 0.3% triethanolamine. The polymer dispersants include 0.8% to 1.5% polycarboxylates and 0.5% to 1% polyacrylates.

5. The formula of environmentally friendly aluminum decorative material based on decomposing formaldehyde by negative ions according to claim 1, characterized in that: Plasticizers include phthalates, aliphatic dibasic acid esters and epoxy plasticizers. Phthalate esters include 3% to 5% dioctyl phthalate and 4% to 6% diisononyl phthalate. Aliphatic dibasic acid esters include 5% to 8% dioctyl adipate and 6% to 9% dioctyl sebacate. Epoxy plasticizers include 5% to 10% epoxidized soybean oil and 4% to 8% epoxy fatty acid methyl ester.

6. The formula of environmentally friendly aluminum decorative material based on decomposing formaldehyde by negative ions according to claim 1, characterized in that: The coupling agent includes a silane coupling agent and a titanate coupling agent. The silane coupling agent includes 0.5% to 1.5% of γ-aminopropyltriethoxysilane and 0.8% to 2% of γ-methacryloxypropyltrimethoxysilane. The titanate coupling agent includes 0.5% to 1% of isopropyltrioleyloxytitanate and 0.6% to 1.2% of isopropyltrititanate.

7. The formula of environmentally friendly aluminum decorative material based on decomposing formaldehyde by negative ions according to claim 1, characterized in that: Antimicrobial agents include inorganic antimicrobial agents, organic antimicrobial agents and natural antimicrobial agents. Inorganic antimicrobial agents include 0.1% to 0.5% silver-based antimicrobial agents, 0.3% to 0.8% copper-based antimicrobial agents and 0.5% to 1% zinc-based antimicrobial agents. Organic antimicrobial agents include 0.2% to 0.6% quaternary ammonium salt antimicrobial agents, 0.1% to 0.3% biguanide antimicrobial agents and 0.1% to 0.4% phenolic antimicrobial agents. Natural antimicrobial agents include 0.5% to 1.5% chitosan and 0.3% to 0.8% plant extracts.

8. The formula of environmentally friendly aluminum decorative material based on decomposing formaldehyde by negative ions according to claim 1, characterized in that: The preparation steps are as follows: Step 1: placing aluminum powder in a drying oven, sieving it through a sieve after drying, grinding tourmaline powder, nano titanium dioxide and negative ion powder with a planetary ball mill, and then mixing them with a dispersant and water, and dispersing them by ultrasonication; Step 2: Add modified resin, plasticizer, stabilizer, dispersant and water into a mixer and stir. Heat appropriately during stirring to form a resin solution. Slowly add the treated tourmaline powder, nano titanium dioxide and negative ion powder into the resin solution in sequence. After mixing evenly, add coupling agent and antibacterial agent and continue stirring for 10 to 15 minutes. Step 3: The mixed material is formed through a twin-screw extruder, and the formed product is placed in an oven for curing. After curing, the product surface is polished with sandpaper to remove burrs and flaws on the surface, and then polished with polishing paste. After polishing, the prepared aluminum environmentally friendly decorative material is tested for performance.

9. The formula of environmentally friendly aluminum decorative material based on decomposing formaldehyde by negative ions according to claim 8, characterized in that: The drying temperature is 80-100°C, the drying time is 2-3h, the sieve aperture is 100-200 mesh, the particle size is ground to 1-5 microns, the dispersion time is 30-60min, the temperature of each section of the extruder is 120-140°C for zone 1, 160-180°C for zone 2, 180-200°C for zone 3, 200-220°C for zone 4, the head temperature is 200-230°C, and the screw speed is 30-50 rpm.

10. The formula of environmentally friendly aluminum decorative material based on decomposing formaldehyde by negative ions according to claim 8, characterized in that: The stirring speed is 600-800 rpm, the stirring time is 10-15 min, the heating temperature is 40-60° C. After adding tourmaline powder, nano titanium dioxide and negative ion powder, the stirring speed is increased to 1000-1500 rpm, and the stirring time is continued for 20-30 min.